1991
DOI: 10.1111/j.1365-2141.1991.tb04376.x
|View full text |Cite
|
Sign up to set email alerts
|

Priming of normal human neutrophils by recombinant human growth hormone

Abstract: Growth hormone (GH) plays an important role in the development, maintenance and function of the immune system. Previous data has demonstrated that GH is also a newly defined macrophage-activating factor. Activation of polymorphonuclear neutrophils (PMN) by GH has not yet been examined. This paper presents studies demonstrating the effects of GH on the migratory behaviour and respiratory burst of PMN. In a modified Boyden chamber chemotaxis assay, GH did not stimulate PMN locomotion when added directly to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 18 publications
(8 reference statements)
2
25
0
Order By: Relevance
“…It is well established that GH is a physiological mediator of immune cell functions (15)(16)(17)(18)(19), and many of the actions of this stimuli are likely to be transduced through the Jak2 pathway (20,21,23). Although it has been reported that GH increases neutrophil adhesion, the possible mechanisms have not been examined (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that GH is a physiological mediator of immune cell functions (15)(16)(17)(18)(19), and many of the actions of this stimuli are likely to be transduced through the Jak2 pathway (20,21,23). Although it has been reported that GH increases neutrophil adhesion, the possible mechanisms have not been examined (16).…”
Section: Discussionmentioning
confidence: 99%
“…GH has been shown to influence the development of the immune organ and the function of immune cells (15)(16)(17)(18)(19). The binding of GH to its receptor causes dimerization of two growth hormone receptor (GHR), which, in turn, initiates the signal transduction in the cell.…”
Section: Regulation Of Neutrophil Adhesion By Pituitary Growthmentioning
confidence: 99%
“…From the peripheral blood of healthy volunteers (anticoagulated with EDTA), PMN were obtained after discontinuous density gradient centrifugation of whole blood on Percoll or from buffy coat residues (mixed with normal saline in a ratio of 3:1) by dextran sedimentation and centrifugation through a layer of Ficoll-Hypaque as described (26), followed by hypotonic lysis of contaminating erythrocytes using sodium chloride solution. The cell preparations (> 95% neutrophils by morphology in Giemsa stains, > 99% viable by trypan dye exclusion) were resuspended in RPMI-1640/0.5% BSA forchemotaxis experiments, or in HBSS for respiration burst activity and exocytosis assays.…”
Section: Introductionmentioning
confidence: 99%
“…NBT reduction by PMN was measured as described (26 Chemotaxis. The chemotactic response of PMN to different gradients of FMLP and/or ANP was tested in a modified multiwell Boyden chamber as previously described (26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation